Occupational health crossing borders part 2: Comparison of 18 occupational health systems across the globe (2010)
Occupational health and safety (OHS) is considered one of the most important factors for a sustainable development; however, it is often considered a luxury by decision‐makers. This article compares OHS systems of 18 countries at different stages of development. In an international summer school, structure of the national OHS system, definition of occupational accidents and diseases, procedures for compensation claims, outcome (expressed as incidence of occupational accidents) and training opportunities were presented. National OHS systems ranged from non‐existent to systems implemented almost 200 years ago. Priorities, incidence of occupational accidents and training opportunities varied. Common problems included the lack of OHS service for small enterprises and in rural areas. International training programs like this summer school might enhance the exchange about OHS opportunities around the globe and contribute to improved workers health.